2021
DOI: 10.3390/plants10071461
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Potential in Water Cleanup from Metals and Nutrients of Desmodesmus sp. and Ampelodesmos mauritanicus

Abstract: Increasing levels of freshwater contaminants, mainly due to anthropogenic activities, have resulted in a great deal of interest in finding new eco-friendly, cost-effective and efficient methods for remediating polluted waters. The aim of this work was to assess the feasibility of using a green microalga Desmodesmus sp., a cyanobacterium Nostoc sp. and a hemicryptophyte Ampelodesmos mauritanicus to bioremediate a water polluted with an excess of nutrients (nitrogen and phosphorus) and heavy metals (copper and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…14 Previous studies have shown that Desmodesmus sp. can be used to remove heavy metals 15 and tetracyclines 16 from wastewater, but there are still few reports on its antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%
“…14 Previous studies have shown that Desmodesmus sp. can be used to remove heavy metals 15 and tetracyclines 16 from wastewater, but there are still few reports on its antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%
“…were used to treat single-metal solution wastewater in a sequential approach, and the Cu and Ni removal rates reached up to 74% and 85%, indicating that Desmodesmus sp. has a better sewage treatment capacity when used in combination with other organisms [ 19 ]. When comparing the removal effects of Chlorella vulgaris, Botryococcus Braunii and Desmodesmus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that Desmodesmus sp. can be used to remove heavy metals [15] and tetracyclines [16] from wastewater, but there are still few reports on its antioxidant capacity.…”
Section: Introductionmentioning
confidence: 99%